Pengaruh Perputaran Modal Kerja dan Likuiditas terhadap Profitabilitas pada Sub Sektor Property dan Real Estate di Bursa Efek Indonesia - Mahardika, Komang Tri Wibawa; Suci, Ni Made (Jurnal Akuntansi Profesi, 2021)
This study aimed to examine the effect simultaneous and partial of working capital turnover and liquidity on profitability. The study design was used quantitative causal. The subject of this study was property and real estate companies listed on the Indonesia Stock Exchange and the object of this study were working capital turnover, liquidity and profitability. The population of this study were 36 companies in the property and real estate sub-sector. Data was collected by documentation recording and analyzed by multiple linear regression analysis. The results showed that (1) working capital turnover and liquidity has significant effect on profitability with a contribution of 72,8%, (2) working capital turnover has positive and significant effect on profitability of 63,5%, (3) liquidity has negative and significant effect on profitability of 31,1%.